Methodology of optimisation of local energy infrastructure development - Zbigniew Juroszek; Mariusz Kudełko (Managerial Economics)
One of the most important issues concerning the national energy policy in Poland is planning of development of municipal energy infrastructure by local authorities. However, many munici- palities do not have strategic plans for supplying local residents and businesses in energy. In addition, those plans that exist are usually very simplified, vague and imprecise. It is mainly due to not applying by local authorities optimizing tools during the planning process (intuition or following of others is the base instead). In this context, research on the possibility of modeling and optimization of local energy systems development seems an interesting and important is- sue. In this paper the authors present a mathematical optimization model which seems to suit well the needs of local authorities with respect to the strategic plans of local energy infrastruc- ture development. The concept of the model may be a good starting point to create a complex, user friendly, easy to learn and municipality oriented software tool for the optimization of local energy infrastructure development.